THE EFFECT OF OFFERED FERMENTED RICE HULL IN RATION SUPPLEMENTED WITH PURPLE SWEET POTATO (Ipomoea batatas L.) LEAF ON LIPID PROFILE OF DUCK MEAT - Susila, T.G. Oka; Yadnya, T.G. Belawa; Roni, Ni Gusti Ketut (Metamorfosa: Journal of Biological Sciences; Vol 4 No 2 (2017)DO - 10.24843/metamorfosa.2017.v04.i02.p08, 2017)
This experiment was carried out to study the effect of offered fermented rice hull in ration supplemented with purple sweet potato ( Ipomoea batatas L.) leaf on lipid profile of duck meat. Seven treatment rations were used in a completely randomized design (CRD) consisted of control ration A (ration   without containing rice hull and purple sweet potato leaf), ration B (ration  containing 5% rice hull), ration C (ration containing 5% fermented rice hull and purple sweet potato leaf ), ration D (ration  containing 10%  rice hull), ration E   (ration containing 10% fermented rice hull and purple sweet potato leaf), ration F (ration containing 15%  rice hull),and ration G (ration containing 15% fermented rice hull and purple sweet potato leaf). Each treatment consisted of three replicates  and each replicate consisted of five ducks. Variable observed in this study  were feed consumption, protein, crude fiber and antioxidant  consumption and lipid profile consisted cholesterol total, HDL, LDL and TGA. The results showed that feed, protein, crude fiber and antioxidant consumption on treatment A were 6414.10., 1027.70., 520.82 and 59,51g/head.  Giving  treatment B, C, D, E, F and G  decrease feed consumption (P, < 0.05), but protein consumption was increase significantly (P <0.05) except for treatment B was not significant compared with treatment A. Giving  treatments C, E and G were decrease crude fiber consumption (P<0.05).  Crude fiber consumption in treatment B increase significantly (P < 0.05), but crude fiber consumption in treatment D and F were not significantly different (P>0.05) with control (A).  Antioxidant consumption for  treatments B, C, D, E, F and G were increase significantly (P<0,05) compared with  A. Lipid profile of duck meat consisted of cholesterol total, HDL, LDL and TGA in treatment A were  75,84., 26,81., 30,04 and 100,87 mg/100g. Offered treatment B, C, E, F and G significantly decrease cholesterol total (P<0.05), but treatment D was not significantly different (P>0.05) with  treatment A . While on HDL and TGA for all treatment were not significantly different (P>0.05) except TGA for treatment C was increase significantly (P<0.05), compared treatment A. Offered  treatment C, E and G  were significantly decease LDL of  duck meat, but   treatment B, D and F   were not significantly different (P<0.05) with treatment A. Its can be concluded that offered fermented rice hull in ration supplemented with purple sweet potato ( Ipomoea batatas L.) leaf improve lipid profile of  duck meat.